Mycobacterium fortuitum from lesions of slaughtered pigs in Ibadan, Nigeria (2010)
To ascertain the cause of tuberculous-like lesions in pigs slaughtered in a local abattoir in Ibadan (south-western Nigeria), a total of 516 pigs were inspected over a period of four months, 18 of which had gross lesions suggestive of tuberculosis at post-mortem. Mycobacterial culture and molecular typing (GenoType® Mycobacterium CM [Common Mycobacteria] assay) analysis were used to identify and confirm the mycobacteria species responsible for these lesions. Results show that 2.3% (12/516) of the animals screened were infected with mycobacteria; Mycobacterium fortuitum was confirmed in 33.3% (4/12) of these cases. As far as the authors are aware, this is the first report confirming the isolation of M. fortuitum in slaughtered pigs in Nigeria. There is a need to improve on necessary preventive and control measures that will reduce potential sources of mycobacterial infections in pig-rearing herds. These infections may also have public health implications, especially to workers in the pig industry.